299 Implementing A Formal Surgical Handover Tool for Junior Doctors – A QI Approach. (4th May 2021) - Gill, E; Quested, S; Lim, J; Mohsin, M
Abstract: Introduction: An informative medical handover facilitates safe patient care. It was recognized that insufficient clinical information at handover resulted in unsafe communication in the general surgical department at Pinderfields General Hospital (PGH). We aim to utilise the Royal College of Surgeons' (RCS) and British Medical Association's (BMA) guidelines to improve the existing handover system, facilitate an efficient and relevant handover, and furthermore improve patient safety. Method: General surgical foundation doctors (FDs) (n = 15) at PGH were surveyed to establish their perspectives of existing handover documentation. Subsequently a handover tool was iteratively designed, using tests of change, combining RCS and BMA guidelines with FDs' suggestions of patient information required for safe handover. At two time points, FDs in the department were re-surveyed to measure improvement. Results: Prior to implementation of a formal document, only 20% of FDs reported sufficient patient identifiers of the handover. This improved to 67% post intervention. Pre-intervention, 0% perceived the handover as 'Excellent', 20% as 'good'. Post-intervention, these improved to 34% and 60% respectively. Conclusions: Over six months, we improved the FD's handover document, resulting in positive feedback of perceived safety of surgical patient handovers. However, recognised time constraints have highlighted the need for more efficient handover documentation.